(untitled) (Research, Society and Development, 2024)
The Covid-19 pandemic had significant impacts on the mental health of people around the world, and new mothers were no different. This study aims to analyze the production of knowledge about the impact of the Covid-19 pandemic on postpartum depression and mother-child bonding. To this end, a survey of articles available in the databases was carried out: Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database and Psychology Index (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE). This search resulted in a total of 2,381 articles, of which only 29 were included, of which 16 were cross-sectional studies; studies with level of evidence VI stand out; with a predominance of articles published in 2022. The effects of the Covid-19 pandemic on women’s mental health were predominantly reported (n=17), followed by studies that addressed the risk factors for PPD during the pandemic (n= 7) and those who described the impacts of the pandemic on the mother-child bond (n=5). Therefore, it was observed that many articles highlighted negative impacts on the health of new mothers during the Covid-19 pandemic, with the prevalence of an increase in the number of depressive symptoms that affected these women, as well as risk factors that can influence them. lo, in addition to perceiving the unfavorable effects on the mother-child bond.